INFOGRAPHIC: INFORMATION DELIVERY MEDIA IN PUBLIC RELATIONSHIP PRACTICES - Fajar Novianto; Marshelia Gloria Narida (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
This article discusses the process of applying infographic criteria by the Sub-Department of Law and Public Relations of the Directorate General of Horticulture (DG Horticulture) as a medium for delivering information to the public. The results of the study showed that there were nine criteria for the process of applying the standards in a collection of good quality infographics at Sub-Department of Law and Public Relations of the Directorate General of Horticulture before infographics could get disseminated to the public. Where in the nine criteria application process, each criterion explains how to focus the media on delivering information that is interesting and easily understood by the public